A Study on Smart System Using IOT for Surveillance of Crop-Field - Kumar Sahoo, Bijoy; Pattanaik, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
Agriculture is considered a significant job for improvement in nourishment production. In our nation, farming relies upon the rainstorm which is not an adequate wellspring of water. So the water system is utilized in the horticulture field. IoT is an achievement in the advancement of innovation. IoT assumes a significant job in numerous fields, one of that is agriculture by which it can encourage billions of individuals on Earth in the future. The target of this paper is planning to conquer this test, the entire system is smaller scale control based and can be worked from a remote area through remote transmission so there is no compelling reason to worry about water system timing according to yield or soil condition. The sensor is utilized to take sensor perusing of soil like soil dampness, temperature, air dampness and basic leadership is constrained by the client by utilizing microcontroller. The information got from sensors is sent to a server database utilizing remote transmission. The water system will be mechanized when the dampness and temperature of the field are diminished. The rancher is advised with the data in regard to handling conditions through portable intermittently. This system will be progressively helpful in regions where there is a shortage of water and will be worth effective in fulfilling its prerequisites.